PERAN KINERJA LABA DALAM MEMODERASI PENGARUH ANTARA CORPORATE SOCIAL RESPONSIBILITY TERHADAP PENGHINDARAN PAJAK - Adhitya Putri Pratiwi; Ani Kusumaningsih (EkoPreneur, 2019)
This research aims to determine the role of earnings performance in moderating the influence of Corporate Social Responsibility to Tax Avoidance. The research methode used was the Analytical Causal Associative with a sample size of 31 mining sector companies listed on Indonesia Stock Exchange in 2015-2018. Data collected in this research  are secondary data using non-participant observation with the analysis tool E-views 9. Based on the results of the reasearch, it was found that Corporate Social Responsibility affects tax avoidance and earning performance is able to strengthen the influence beetwen Corporate Social Responsibility On Tax Avoidance. Keywords : Corporate Social Responsibility, Profit Performance, Tax Avoidance